Transcatheter Management of Pulmonary Sequestrations in Children-A Single-Center Experience - Ibrahim Abu Zahira; Raymond N. Haddad; Mathilde Meot; Damien Bonnet; Sophie Malekzadeh-Milani (MDPI AG, 2023)
Background: A pulmonary sequestration (PS) is an area of bronchopulmonary tissue with aberrant arterial supply. Transcatheter occlusion of PSs is an appealing treatment option, but data on outcomes remain scarce. We aim to describe our experience with transcatheter management of PS in infants and children. Methods: Retrospective review of clinical data of all patients with suspected PS sent for diagnostic and/or interventional cardiac catheterization at our institution between January 1999 and May 2021. Procedural considerations, techniques, standard safety, and outcomes were assessed. Results: We identified 71 patients (52.1% males), with median age and weight of 4.9 months (IQR, 2.1-26.6) and 4.2 kg (IQR, 3.9-12.1), respectively. Sixty-one (86%) patients had associated congenital heart defects (CHDs). Forty-two (59%) patients had pulmonary arterial hypertension (PAH) at the time of diagnosis. Fifty-three (74.7%) patients underwent embolization of the PS feeding vessel using microcoils and/or vascular plugs, and eight (15.1%) of these were neonates who presented with severe PAH and cardiac failure. Two patients had large feeding vessels and were treated surgically. Sixteen (22.5%) patients with small feeding vessels received conservative management. At median follow-up of 36.4 months (IQR, 2.1-89.9), seven patients had died, 24 patients had CHD corrective surgeries, 26 patients had redo catheterizations, and five patients had persistent PAH. No PS surgical resection was needed, and no infection of the remaining lung tissue occurred. Conclusions: Transcatheter assessment and treatment of PSs is a safe and effective procedure. Neonates with large PSs are severely symptomatic and improve remarkably after PS closure. PS embolization and surgical repair of associated CHDs generally leads to the normalization of pulmonary pressures.